2013
DOI: 10.4028/www.scientific.net/nh.5.1
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost pH Sensor Based on RuO<sub>2</sub> Resistor Material

Abstract: Abstract. Fresh water deficiency caused by climate change calls for employing novel measures to ensure safety of drinking water supply. Wireless sensor networks can be used for monitoring hydrological conditions across wide area, allowing flow forecasting and early detection of pollutants.While there are no fundamental technological obstacles to implementation of large area sensor networks, their feasibility is constrained by unit cost of sensing nodes. This paper describes a lowcost pH sensor, intended for us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…MO x have recently gained increasing interest for electrochemical and biosensing applications due to their unique electrical, electrochemical and highly sensitive properties which assert their utility in healthcare and water and food quality monitoring applications. 32,[187][188][189] Due to high surface to volume ratio, the morphology of nano structured MO x enhances the sensitivity, response time, selectivity and catalytic activity of sensitive electrodes. 47 For example, in comparison to ZnO nanorods (sensitivity 28.4 mV pH À1 ) ZnO nanotubes show high sensitivity (45.9 mV pH À1 ) due to their low dimensionality and higher levels of surface and subsurface oxygen vacancies.…”
Section: Flexible Sensitive Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…MO x have recently gained increasing interest for electrochemical and biosensing applications due to their unique electrical, electrochemical and highly sensitive properties which assert their utility in healthcare and water and food quality monitoring applications. 32,[187][188][189] Due to high surface to volume ratio, the morphology of nano structured MO x enhances the sensitivity, response time, selectivity and catalytic activity of sensitive electrodes. 47 For example, in comparison to ZnO nanorods (sensitivity 28.4 mV pH À1 ) ZnO nanotubes show high sensitivity (45.9 mV pH À1 ) due to their low dimensionality and higher levels of surface and subsurface oxygen vacancies.…”
Section: Flexible Sensitive Electrodesmentioning
confidence: 99%
“…32 However, for exible and wearable pH sensors, the application of these oxides, especially RuO 2 , is limited due to the lack of biocompatibility, exibility, high cost and high temperature processing required. 32,188,191 The sensitivity of MO x based pH sensors largely depends on the material composition and the method used for material deposition because the microstructure, porosity, surface homogeneity and crystalline structure of the material inuences the sensing performance (Table 3). 32,191,192 It has been demonstrated that IrO 2 has very good biocompatibility and proved its cell viability close to 100% which is higher than indium tin oxide (ITO).…”
Section: Flexible Sensitive Electrodesmentioning
confidence: 99%
“…Potentiometric pH sensors employing metal oxide thin film sensing electrodes offer an alternative to pH-FETs and traditional glass pH probes, due of their small-footprint, cost effectiveness and ease to manufacture [8]. Of the numerous metal oxides that exhibit pH sensitivity, RuO 2 has been widely investigated due to its excellent corrosion resistance, thermal stability, high sensitivity, low hysteresis and low resistivity in comparison with other metal oxides (Table 1) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Of the numerous metal oxides that exhibit pH sensitivity, RuO 2 has been widely investigated due to its excellent corrosion resistance, thermal stability, high sensitivity, low hysteresis and low resistivity in comparison with other metal oxides (Table 1) [8,9]. RuO 2 has also demonstrated excellent biocompatibility in cell studies and has been used for the construction of neural electrodes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1, the structure consists of Ag/AgCl reference electrode, AgPd working electrode, KCl electrolyte, Ruthenium based active layer and temperature sensor, and dielectric passivation layer. The use of Ruthenium as an active layer for pH sensor has been demonstrated [19] in the previous work. The minimum linewidth and spacing for the conductive electrode tracks and resistive temperature sensor are 300 Pm and 500 Pm, respectively.…”
Section: Design and Fabricationmentioning
confidence: 99%